The Land Legal System in Indonesia and Land Rights According to the Basic Agrarian Law (UUPA) - Sugina Hidayanti; Indra Koswara; Yopie Gunawan (LEGAL BRIEF, 2021)
After the enactment of Law No. 5 of 1960 concerning Agrarian Principles, this article aims to explain the Indonesian agrarian law system. The law focuses on the unification of agrarian regulations in Indonesia in order to create a unified agrarian legal system. The Agrarian Principle must highlight that all people have access to their lands in order to secure their happiness and prosperity, as well as to ensure that the people are treated fairly. According to Article 6 of the law, every piece of land must serve a social purpose, namely, to generate goods for the people. This article also seeks to determine if the Agrarian Principles have provided individuals, the state, and members of customary law with legal clarity over certain land rights.